Korelasi Pemberian Terapi Bermain Mewarnai Gambar terhadap Dampak Penurunan Stres Akibat Hospitalisasi pada Anak Usia Pra Sekolah: Review of Evaluation Results of Children's Character Education in PAI Learning - Mulyana, Asep; Darusman, Septiandi Eka; Wahyudi, Deni (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Hospitalization is a critical condition in children, when children are sick and hospitalized as a threatening experience and become a stressor that can cause a crisis for children and families. Efforts to reduce the impact of children due to hospitalization experienced by children during the childcare period, a medium is needed that can express anxiety, one of which is coloring picture play therapy. The purpose of this study was to analyze the effect of providing coloring picture play therapy on reducing stress due to hospitalization in preschool children. This research method uses a pre-experimental design with a one-group pretest-posttest design. One-group pre-post test design to obtain data on stress levels before and after the intervention. The number of samples in this study was 32 preschool children who met the inclusion criteria. The instrument used for data collection used a questionnaire, then the data was analyzed using a paired t-test. The results showed that the average stress in children due to hospitalization before the intervention was 21.09 points or included in the moderate category and after the intervention it became 13.13 or included in the moderate category. So, it is concluded that there is an effect of providing coloring picture play therapy on reducing stress due to hospitalization in preschool children with a p value of 0.000. Coloring picture play therapy can be effective in reducing stress in children due to hospitalization, therefore health workers can apply coloring picture play interventions to children who are hospitalized.